A Case Report of Marfan Syndrome with Literature Review - Hemanth Kumar Kalla; Swarna Kumari; CH Rama Rao; MKR Parthasarathy; S Surya Prakash Reddy; M Revathi (International Journal of Public Health Science (IJPHS), 2015)
Marfan syndrome(MFS) is a connective tissue disorder that affects multiple organ systems. Cardiovascular, ocular, and skeletal abnormalities are cardinal features of the syndrome. Its incidence is among the highest of any heritable disorder.Most patients who have Marfan syndrome are usually diagnosed incidentally when they present for a routine physical examination for various reasons. The purpose of this paper is to provide a review of the literature, as well as describe a 22-year-old male with MFS and right hydroureteronephrosis diagnosed incidentally when he attended our hospital for complaints of fever and right loin pain. This case report emphasizes importance of “Revised Ghent criteria” for the diagnosis of MFS and highlights various clinical signs of MFS.